–21 + x
Explanation:
Step 1: Given expression: –4 + (–17) + x
Step 2: In the algebraic property, positive × negative = negative
So, –4 + (–17) + x = –4 – 17 + x
Step 3: Add two negative numbers, the result will be sum with minus sign
–4 – 17 + x = –21 + x
Hence, –21 + x is the required equation.
Answer:
x- intercept = - 8, y- intercept = 6
Step-by-step explanation:
To find the x- intercept let y = 0 and solve for x
- 3x + 4(0) = 24
- 3x = 24 ( divide both sides by - 3 )
x = - 8 ← x- intercept
To find the y- intercept let x = 0 and solve for y
- 3(0) + 4y = 24
4y = 24 ( divide both sides by 4 )
y = 6 ← y- intercept
In order to prove this, you simply plug in the number 2 everywhere you see X:
4^(2) = 8(2).
Simplify
16 = 16 √
Since this checks out, x is proven to be 2.
Answer: I think I cn help bt nt sure
Step-by-step explanation:
X° + 52° + 78° = 180°
X° + 130° = 180°
X° + 130° - 130° = 180° - 130 °
X° = 50°
M is <50°
Answer:
Fraction Form: (-1/2)
Decimal Form: (-0.5)
Step-by-step explanation: